Pengaruh Lamanya Inokulasi Parasitoid Sturmiopsis inferens Town (Diptera: Tachinidae) terhadap Jumlah Inang Phragmatocia castaneae Hubner (Lepidoptera: Cossidae) di Laboratorium The Influence of Inoculation Periode Parasitoid Sturmiopsis inferens Town (Di - Tetra Febryandi Sagala; Maryani Cyccu Tobing; Lisnawita Lisnawita (Universitas Sumatera Utara, 2015)
The objectives of the research was to study the capability of S. inferens (Diptera: Tachinidae) afterinoculated on larvae P. castaneae Hubner (Lepidoptera: Cossidae) with different types of theinoculation period and larvae numbers. The research was conducted in Laboratory of SugarcaneResearch and Development Sei Semayang, Binjai, Medan, North Sumatera from November 2013until January 2014. The method used Randomized Complete Design with two factors and threereplications, the first factor was larvae number (30, 40, 50 larvae P. castaneae) and the secondfactor was inoculation period (25, 35, 45 minutes). The results showed that inoculation period,larvae numbers and interaction of both did not effected tobe become imago. Sex ratio of S. inferenseffected on progeny producted with male and female 1.1 : 1.0Keywords: inoculation, parasitoid, Sturmiopsis inferens, Phragmatocia castaneae.